The efficacy of neoadjuvant immunotherapy and lymphocyte subset predictors in locally advanced esophageal squamous cell carcinoma: A retrospective study - Ruotong Wang; Shaodi Wen; Xiaoyue Du; Jingwei Xia; Bowen Hu; Yihan Zhang; Guoren Zhou; Feng Jiang; Xiaomin Lu; Miaolin Zhu; Xinyu Xu; Bo Shen (Cancer Medicine)
Abstract Background Despite the recognized therapeutic potential of programmed cell death protein 1/programmed death‐ligand 1 (PD‐1/PD‐L1) inhibitors in advanced esophageal squamous cell carcinoma (ESCC), their role in neoadjuvant therapy and reliable efficacy biomarkers remain elusive. Materials and Methods We retrospectively analyzed locally advanced ESCC patients who underwent surgery following a 2‐cycle platinum and paclitaxel‐based treatment, with or without PD‐1 inhibitors (January 2020–March 2023). We assessed peripheral blood indexes and tertiary lymphoid structures (TLS) density to evaluate their impact on pathological response and prognosis, leading to a clinical prediction model for treatment efficacy and survival. Results Of the 157 patients recruited, 106 received immunochemotherapy (ICT) and 51 received chemotherapy (CT) alone. The ICT group demonstrated a superior pathological response rate (PRR) (47.2% vs. 29.4%, p = 0.034) with comparable adverse events and postoperative complications. The ICT group also showed a median disease‐free survival (DFS) of 39.8 months, unattained by the CT group. The 1‐year DFS and overall survival (OS) rates were 73% and 91% for the ICT group, and 68% and 81% for the CT group, respectively. We found higher baseline activated T cells, lower baseline Treg cells, and a decreased posttreatment total lymphocyte and CD4+/CD8+ ratio predicted an enhanced PRR. Reduced posttreatment CD4+/CD8+ ratio and increased NK cells were associated with prolonged survival, while higher TLS density indicated poorer prognosis. Among ICT group, a lower posttreatment CD4+/CD8+ ratio indicated longer DFS and reduced posttreatment B cells indicated longer OS. A nomogram integrating these predictors was developed to forecast treatment efficacy and survival. Conclusion The combination of PD‐1 inhibitors and chemotherapy appears promising for locally advanced ESCC. Evaluating the differentiation status and dynamic changes of peripheral blood immune cells may provide valuable predictive insights into treatment efficacy and prognosis.